PEMBENTUKAN KARAKTER ANAK BERBASIS ISLAMIC CORE VALUE - faizatul Husna; Syaiful Islam (STAI Tuanku Tambusai, 2019)
Islamic education is an important component in forming the character of a child because Islamic religious education is the foundation that will color the life that children will go through. Meanwhile the number of fights between adolescents, immoral acts among young people, promiscuity, the growth of adultery, consuming illegal drugs is caused by the lack of supervision from the family which makes them so easy to use and do it. By using qualitative methods with interviewing techniques the author wants to know how the Islamic religious education strategy is applied to the family. From the results of interviews with one family that Islamic religious education in families in shaping children's character uses 6 strategies, namely: 1) exemplary strategies, 2) habituation strategies, 3) counseling strategies, 4) disciplinary strategies, 5) punishment strategies, and 6) gift giving strategy. To shape the character of the child in order to become a man of faith and devotion to the Almighty God, as well as a noble character that includes ethics, morality, character, spirituality cannot be separated from the role of the family played by parents because the family is the first and foremost educational institution for children.